Evaluasi Sistematis Efisiensi Turbin Angin Lepas Pantai Terapung dan Potensi Reduksi Emisi Karbon - Salsabila, Salma; Prasetyo, Sigit; Wicaksana, Putra Adil; Sa’Diah, Siti Dhurrotus; Dzaky Abdad, Muhammad Rafif; Trisnoaji, Yuki (CV. IRA PUBLISHING, 2025)
The growing demand for clean energy has accelerated interest in Floating Offshore Wind Turbines (FOWTs), which enable efficient wind energy harvesting in deep-water regions. This study conducts a systematic literature review across four major databases, Scopus, ScienceDirect, SpringerLink, and Google Scholar, to evaluate the energy efficiency, carbon emission reduction potential, and economic feasibility of FOWT systems. The findings indicate that combined configurations, such as Spar–TLP and multi-turbine platforms, provide the highest energy conversion performance and structural stability, contributing to up to 17% in carbon emission reduction. Economically, several studies report competitive Levelized Cost of Energy (LCOE) and relatively short payback periods. This research strengthens the understanding of FOWT performance by integrating global evidence into the context of marine energy sustainability. However, methodological limitations arise from data variability across studies and the dominance of simulation-based analyses. Further research is required to optimize mooring systems and adapt FOWT designs to tropical and archipelagic environments, such as those found in Indonesia.